Vegetation Index and Mangrove Forest Utilization through Ecotourism Development in Dodola and Guraping of North Maluku Province - Yerik Afrianto Singgalen (Institut Pertanian Bogor (IPB University), 2022)
This study analyzes the vegetation index and mangrove forest utilization through ecotourism development in Guraping and Dodola Island of North Maluku Province. This research uses a remote sensing approach through Landsat 8 Operational Land Immaginer (OLI) from 2013 and 2021, calculated based on the Normalized Difference Vegetation (NDVI) algorithms. This study indicates that ecotourism development can preserve the mangrove forest and generate the economic and social benefit of the local community. Otherwise, the vegetation index in mangrove areas from 2013-2021 needs to be considered seriously as the primary data to optimize the management of tourism destinations. Through the case of Dodola Island, the increased number of vegetation in 2017 experienced significant changes and threatened the sustainability of mangrove ecotourism. Thus, the mangrove monitoring needs to be optimized to anticipate the unsustainability of mangroves, which determines the sustainability of tourism in North Maluku Province. This study offers an idea to involve the local community in conserving the mangrove area through a controlled and sustainable rehabilitation program instead of economic activity purposes. The findings indicate that the existing condition of the Guraping mangrove forest in 2021 is classified as moderate compared with mangrove ecotourism in Dodola Island with sparse criteria based on the Decree of the Minister of State for the Environment in 2004, This research suggests adopting the community-based ecotourism mangrove development through collaborative advantages of all tourism stakeholders.